Cancel culture o decolonizzare i saperi e la cultura? - Miguel Mellino (Cambio)
In recent decades, the intense development of feminist, anti-racist and indigenous peoples’ movements has given rise to a profound struggle as much for the reconstitution in a more egalitarian sense of traditional material relations of domination as for the political and cultural dissolution and resignification of those colonial, racial and patriarchal hierarchies that have shaped single spheres of modern social life since the rise of western capitalist modernity. The dimension of such a global movement could not but raise the question of the existence of a centuries-old white privilege underlying the very linguistic and cultural signification of the modern social world and its dominant systems of classification and representation. Our paper will attempt to highlight three issues, which we feel are important in order to understand the real stakes behind the accusation of ‘cultures of erasure’ levelled at these movements: (a) the existence of a modern white privilege to be understood as a ‘total social fact’, (b) the symptomatic nature of the very emergence of the ‘cancel culture’ paradigm, i.e. its constitution as a reaction of that same white privilege to the emergence of other positionings, knowledge, narratives and systems of representations that are entirely external to its historical, economic, ontological and political grammar.